HEMODYNAMIC EFFECTS OF LATERAL TILT BEFORE AND AFTER SUBARACHNOID BLOCK DURING CAESAREAN DELIVERY. - Hubba Ahmed; Muhammad Arsalan Jamil; Hajra Zafar Siddiqui; Umama Masnoon; Muhammad Nauman Aqeel; Shaista Uzair (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Supine hypotension during cesarean delivery under spinal anesthesia is a common clinical challenge caused by aortocaval compression by the gravid uterus, leading to decreased cardiac output and hypotension. The study aims to evaluate the impact of a 15 degree left lateral tilt on hemodynamic variables, including mean arterial pressure (MAP) and heart rate (HR), before and after spinal anesthesia and following fetal delivery, in a resource-limited setting.Methodology: A prospective observational study was conducted on 55 term pregnant women at Dow University of Health Sciences, Pakistan. Patients were positioned supine and with a 15 degree left lateral tilt. Hemodynamic parameters were measured before and after subarachnoid block using standard monitors. Statistical analysis was performed using paired t-tests and ANOVA, with significance set at p < 0.05.Results: The 15-degree lateral tilt significantly improved MAP and HR compared to the supine position before and after spinal anesthesia (p < 0.05). The incidence of hypotension, dizziness, pallor, and nausea was markedly lower in the lateral tilt position post-block and post-delivery. Vasopressor usage was reduced to 23.21%.Conclusion: The 15 degree lateral tilt is an effective, non-pharmacological intervention for mitigating hemodynamic disturbances during cesarean delivery under spinal anesthesia. It enhances maternal cardiovascular stability and reduces adverse symptoms, particularly in resource-constrained settings. Further research is needed to validate these findings in broader populations.